Optimisation of Biodegradable Plastic from Cassava Peel Starch with Additional Materials of Sugarcane Bagasse Cellulose - Rahim, Herlina; Masda, Raehana Ramadhani; Al Adawiyah, Syardah Ugra; Lestari, Mega Fia (Journal of Chemical Process Engineering, 2024)
The use of plastic in large quantities causes environmental pollution because it is not easily decomposed. One way to overcome this is to make bioplastics from natural materials that are easily decomposed such as cassava peel starch. However, the use of starch in making bioplastics still has low mechanical properties. Therefore, cellulose is added as an additive to improve the mechanical properties of bioplastics. This study investigated the potential of cassava peel starch modified with bagasse cellulose as a base material for bioplastics. The aim is to improve the mechanical performance and biodegradability of bioplastics to reduce the environmental impact of conventional plastics. The resulting bioplastics were evaluated based on water absorption, biodegradability, tensile strength, elongation, and elastic modulus tests. Variations in cellulose content showed a significant effect on the physical and mechanical properties of bioplastics. The addition of 18% cellulose provided the best water resistance, while 3% cellulose content resulted in the highest biodegradability. Optimal mechanical properties were achieved at 9% cellulose addition, with a tensile strength of 10.48 N/mm², elongation of 7.92%, and elastic modulus of 3.43 N/mm². However, these results are still below the standards for environmentally friendly plastics based on SNI 7188.7:2016 and SNI 7818:2014, which set higher parameters for water resistance, tensile strength, and elasticity. This bioplastic has the main advantage of being easily biodegradable, making it a potential alternative for certain applications.